Is Sentinel Lymph Node Biopsy Feasible in Multicentric Breast Cancer? A Case Report and Literature Review - Mihaela Camelia Tîrnovanu; Elena Cojocaru; Vlad Gabriel Tîrnovanu; Elena Țarcă; Loredana Toma; Bogdan Florin Toma; Sorana Anton; Ștefan Dragoș Tîrnovanu; Roxana Ana Covali; Cipriana Ștefănescu; Irena Cristina Grierosu (Life)
Accurate lymph node staging is crucial for both prognosis (in the event of early-stage disease) and treatment (for local control of disease) in patients with breast cancer. Sentinel lymph node biopsy (SLNB) has been studied in numerous international trials, showing that it allows about 70% of axillary lymph node dissection (ALND) to be avoided and thus significantly reduces the morbidity associated with ALND. SLNB represents a necessary step in the diagnostic algorithm for breast neoplasms because the surgical treatment for breast cancer has become progressively less invasive. We present a case of a 70-year-old woman with multicentric breast cancer (MBC) treated by surgery at “Cuza Vodă” Women’s University Hospital, Iassy, Romania. In this case, only the ultrasonography established the diagnosis of left MBC with certainty. Conclusion: The detection of sentinel lymph nodes (SLNs) for MBC must be indicated. In this type of cancer, SLNB is accurate and practical, with sufficient quality control and interdisciplinary collaboration between surgical, nuclear medicine, and pathology units. Lymphoscintigraphy allows the patient to avoid axillary clearance surgery if the sentinel node is negative for metastatic disease. The variability of Ki67, PR, HER2, and ER status supports the idea that all individual foci should be tested in MBC cases to provide the best management and prognosis.